2000
DOI: 10.1007/pl00008667
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two glycosyltransferases involved in early glycosylation steps during biosynthesis of the antitumor polyketide mithramycin by Streptomyces argillaceus

Abstract: A 2,580-bp region of the chromosome of Streptomyces argillaceus, the producer of the antitumor polyketide mithramycin, was sequenced. Analysis of the nucleotide sequence revealed the presence of two genes (mtmGIII and mtmGIV) encoding proteins that showed a high degree of similarity to glycosyltransferases involved in the biosynthesis of various antibiotics and antitumor drugs. Independent insertional inactivation of both genes produced mutants that did not synthesize mithramycin but accumulated several mithra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 29 publications
0
48
0
2
Order By: Relevance
“…However, CmmGI and CmmGII are excluded for this role, since mutations of the respective genes do not affect the incorporation of L-chromose B, leaving either CmmGIII or CmmGIV as candidates. Some other antibiotic gene clusters also have fewer glycosyltransferase genes than expected, for example, the mithramycin (4,8), landomycin (29), and aclacinomycin (12) gene clusters. In the latter case, it was shown that the transfer of the second and the third deoxysugar of the trisaccharide chain was carried out by the same glycosyltransferase (12).…”
Section: Discussionmentioning
confidence: 92%
“…However, CmmGI and CmmGII are excluded for this role, since mutations of the respective genes do not affect the incorporation of L-chromose B, leaving either CmmGIII or CmmGIV as candidates. Some other antibiotic gene clusters also have fewer glycosyltransferase genes than expected, for example, the mithramycin (4,8), landomycin (29), and aclacinomycin (12) gene clusters. In the latter case, it was shown that the transfer of the second and the third deoxysugar of the trisaccharide chain was carried out by the same glycosyltransferase (12).…”
Section: Discussionmentioning
confidence: 92%
“…MTA and its secondary metabolite MSK were isolated and purified from the producing organisms as described previously (25,26). Stocks of MTA or MSK were prepared as 1 mmol/L solutions in sterile 150 mmol/L NaCl, maintained at -20jC, and brought to the final concentration just before use.…”
Section: Methodsmentioning
confidence: 99%
“…[3,8] Increasing the length or steric bulk of the N-acyl side chain of 1 a decreases cell-surface expression of the corresponding sialic acids. [10] A rate-determining step in the de novo biosynthesis of unnatural sialic acids appears to be the phosphorylation of ManNAc at the 6-OH by ManNAc 6-kinase.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Surprisingly, saccharide extension reactions have so far been investigated to only a much smaller extent, although for a number of bioactive oligosaccharide-conjugated natural products, among them mithramycin and vancomycin, extending glycosyltransferases (GTs) have been identified. [3,4] However, none of those GTs available has so far been used to elongate natural products' saccharide chains beyond the wild-type length. Here, we report the in vivo conversion of a natural-product trisaccharide into an artificial tetrasaccharide side chain.…”
Section: Introductionmentioning
confidence: 99%